ChemInform Abstract: Luminescent Copper(I) Complexes with Halogenido‐Bridged Dimeric Core. Issue 6 (21st January 2016) - Tsuge, Kiyoshi; Chishina, Yuko; Hashiguchi, Hanako; Sasaki, Yoichi; Kato, Masako; Ishizaka, Shoji; Kitamura, Noboru
Abstract: Review: 145 refs.